Embung Development for Palm Oil Industry Water Supply Based on Soil Water Assessment Tools - Muzhaffar Harits; Asep Sapei; Nora Herdiana Pandjaitan (JURNAL SUMBER DAYA AIR, 2025)
The water supply at the IPB Education and Research Garden Jonggolis generally sourced from rainfall. This can lead to water shortage during certain periods, so building a water storage structure such as a small reservoir (embung) is necessary. The embung can provide a more stable water supply by storing rainwater and river inflow. This research aims to design an embung at the IPB Education and Research Garden Jonggol, and to analyze the water balance of the planned embung. This study presents the application of SWAT-based dependable discharge analysis for small-scale industrial reservoirs in tropical regions. The findings support sustainable water management and enhance enhance agro-industrial resilience, particularly in regions dependent on rainfall. The planned embung is designed for the palm oil processing plant with a total water requirement of 8,786 m3 in the dry season. Dependable discharge analysis is conducted using Soil Water Assessment Tool (SWAT), while flood discharge analysis uses the rational method. Embung capacity design is based on water availability, water requirement, sediment volume, and total evaporation. The planned embung will be located at coordinates 107° 2' 10.53" E and 6° 28' 17.60" S. It features a normal water surface area of 7,737.19 m², a normal water depth of 3 m, and a total storage volume of 9,947.76 m³. The design includes essential components such as an overflow channel, an outlet channel, and an embankment. The water balance indicates that the embung will begin filling in February and remain full from March to May. Subsequently, the water balance is expected to repeat its cycle consistently, ensuring that the embung can meet the water demand at the location.